Histoanatomical changes in pulmonary interstitium in chronic air pollutant exposure- A cross-sectional study. - Pravi, Amrita; Sinha, Neelam; Prasad, Rashmi (Student's Journal of Health Research Africa, 2025)
Background Abnormal collagen deposition, interstitial proliferation, inflammatory cell infiltration, and occasionally lung fibrosis are characteristics of a variety of disorders together referred to as interstitial lung disease (ILD). Objectives- The study's objective is to analyze the histoanatomical changes in the pulmonary interstitium of IPF patients and determine if these changes are related to long-term exposure to occupational and environmental air pollution. Materials and methods It was a prospective, observational study. The study was carried out at the Nalanda Medical College and Hospital (NMCH), Patna, Bihar, India. The study was conducted for 12 months. In all, 150 patients were enrolled in the study. Participants had to be at least 40 years old, have been diagnosed with IPF, have had histopathological confirmation of the disease through autopsy, transbronchial lung biopsy, or surgical lung biopsy, have enough lung tissue samples available for microscopic examination, and have given their informed consent for participation and the use of clinical data and tissue specimens for research. Results Patients who received a lung transplant did so at an average age of 58.1 ± 7.5 years, whereas the average age at death was 71.4 ± 7.9 years. Out of the 150 patients, 25 (16.7%) had exposure to organic dust. The most frequent cause of these, involving 15 patients (10.0%), was farming-related activities. Four patients (2.7%), two (1.3%), and two (1.3%) were found to have been exposed to wood dust, flour dust, and cotton dust, respectively. Conclusion The findings of this study demonstrate that a considerable percentage of individuals with idiopathic pulmonary fibrosis have previously been exposed to organic or inorganic air pollution at work. Recommendations As this was a short-term study, further research is needed with a longitudinal study design and a larger sample to achieve more definitive results.